Prophet Muḥammad صلى الله عليه وسلم: the archetype of mercy - Ahmed, Zakir; Elatrash, Radwan Jamal Yousef; Osmani, Noor Mohammad (IIUM, IRKHS, 2021)
If we were to select one overarching term that defines the nature and mission of the Prophet Muḥammad صلى الله عليه وسلم, it would surely be mercy. Mercy is what Allah جل جلاله uses in the Qurʾān to describe His beloved messenger صلى الله عليه وسلم. He جل جلاله states: ﴿وَمَآ أَرْسَلْنَٰكَ إِالَّ رَحَْْةًۭ ل لْعَٰلَمِينَ۞﴾ We have sent you ˹O Prophet˺ only as a mercy for the whole world.4 Throughout his blessed life, the noble Prophet صلى الله عليه وسلم embodied compassion in every way possible and spread it to every person, animal, place, and object that he met. Those who opposed him were not excluded from experiencing his mercy and even those who did not interact with him were either recipients of his compassion or benefactors of his mercy in some manner, whether directly or indirectly. We are living through turbulent times in our world today and humanity is in much need of compassion. There is clearly a shortage of mercy in the lives of many individuals and societies. Violence, war, corruption, injustice, social and political discord, and other kinds of unrest are all too common everywhere we look. For this reason, it is imperative that people of all walks of life, study the prophetic embodiment of mercy and compassion. The researchers will use the inductive method in order to collect the texts spread out in various old and contemporary books related to the subject, and then the analytical method to extract the most important issues related to mercy. The results of the research: When examining the life of the prophet of mercy, it is effortless to understand the ways in which he brought harmony between people of different views and backgrounds. Studying the biography of the Prophet Muhammad helped to achieve security, peace, and justice in the hearts of people, believers and unbelievers amidst many hardships and challenges.